Association between victimization by bullying and direct self injurious behavior among adolescence in Europe: a ten-country study - Brunstein-Klomek, Anat; Brunner, Romuald; Kaess, Michael (European child & adolescent psychiatry, 2016)
Previous studies have examined the association between victimization by bullying and both suicide ideation and suicide attempts. The current study examined the association between victimization by bullying and direct-self-injurious behavior (D-SIB) among a large representative sample of male and female adolescents in Europe. This study is part of the Saving and Empowering Young Lives in Europe (SEYLE) study and includes 168 schools, with 11,110 students (mean age = 14.9, SD = 0.89). Students were administered a self-report survey within the classroom, in which they were asked about three types of victimization by bullying (physical, verbal and relational) as well as direct self-injurious behavior (D-SIB). Additional risk factors (symptoms of depression and anxiety, suicide ideation, suicide attempts, loneliness, alcohol consumption, drug consumption), and protective factors (parent support, peer support, pro-social behavior) were included. The three types of victimization examined were associated with D-SIB. Examination of gender as moderator of the association between victimization (relational, verbal, and physical) and D-SIB yielded no significant results. As for the risk factors, depression, but not anxiety, partially mediated the effect of relational victimization and verbal victimization on D-SIB. As for the protective factors, students with parent and peer support and those with pro-social behaviors were at significantly lower risk of engaging in D-SIB after being victimized compared to students without support/pro-social behaviors. This large-scale study has clearly demonstrated the cross-sectional association between specific types of victimization with self-injurious behavior among adolescents and what may be part of the risk and protective factors in this complex association.
Gesehen am 20.05.2020